A Comparative Study: Importance of Machine Learning and Deep Learning in the Field of Artiﬁcial Intelligence - Mrudanng Pandya, Dr. Sunil Jardosh, Dr. Amit Thakkar (International Journal of Advanced Science and Technology, 2020)
In this era of computational intelligence we are working for machine-human interaction or more towards putting intelligence into the machines. For this propose, Artiﬁcial Intelligence, Machine learning and Deep learning play a very vital role. AI (Artiﬁcial Intelligence) shows promising results towards the goal which is mention earlier. For improvement of AIs different application results, Machine Learning (ML) and Deep Learning (DL) plays an important role. Today’s information world data size becomes very large, so for data analysis, Deep Learning can become a very crucial part. Our comprehensive analysis provides profound insights into the challenges and applications of AI and ML and how DL can able to solve their limitations.